Epistemology of Prison Interpretation: Analysis of Hamka and Sayyid Qutb’s Political Thoughts - Huda, Nurul (IAIN Pekalongan, 2021)
This article reviews the epistemology of the works of interpretation generated from prison rooms. Hamka and Qutb have similarities in their life struggles. Their presence in prison greatly influences the pattern of their phenomenal works in the field of interpretation, Al-Azhar and Fi Zilal al-Qur'an. The objective of writing this article is to make a typification through a hermeneutic-philosophy-based approach. From the analysis carried out, we find a conclusion that each character, even though both are in prison, both have differences and similarities in the character of the work produced. This can be seen from his interpretation of the verses concerning politics. A comparative analysis shows that three domains characterize the prison interpretation of the two: first, the interpretation is generated from a strong psychosocial aspect of the author's affection; second, the interpretation contains more explanations that are building a system of action; Third, the difference in interests in writing commentaries is caused by the external and internal background of the writer's life.